2020 IEEE International Conference on Robotics and Automation (ICRA) 2020
DOI: 10.1109/icra40945.2020.9197271
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy Resolution Integrated Model Predictive Control of CDPRs: Concept, Implementation and Experiments

Abstract: This paper introduces a Model Predictive Control (MPC) strategy for fully-constrained Cable-Driven Parallel Robots. The main advantage of the proposed scheme lies in its ability to explicitly handle cable tension limits. Indeed, the cable tension distribution is performed as an integral part of the main control architecture. This characteristic significantly improves the safety of the system. Experimental results demonstrate this advantage addressing a typical pick-and-place task with two different scenarios: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…To overcome this problem, a Model Predictive Control (MPC) strategy was introduced in our preliminary work [28]. As highlighted in [29], MPC is one of the few control strategies able to handle system constraints explicitly.…”
Section: Cables Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, a Model Predictive Control (MPC) strategy was introduced in our preliminary work [28]. As highlighted in [29], MPC is one of the few control strategies able to handle system constraints explicitly.…”
Section: Cables Platformmentioning
confidence: 99%
“…As highlighted in [29], MPC is one of the few control strategies able to handle system constraints explicitly. Thus, the Linear MPC (LMPC) introduced in [28] integrates the cable tension distribution calculation within its formulation. Experimental results showed that this MPC is not prone to the aforementioned feasibility issues since it can operate on the WFW boundary without failure.…”
Section: Cables Platformmentioning
confidence: 99%
“…(1) was implemented as part of a position tracking control strategy. More precisely, the Model Predictive Control (MPC) strategy proposed by the authors in [14] was implemented and used to perform the trajectory illustrated in Figure 10. The resulting measured cable tensions and cable tension tracking errors are shown in Figure 11.…”
Section: Main Validationmentioning
confidence: 99%
“…It should be noted that the proposed formulation of MPC with embedded integrator includes in the cost function the variation of the cable tensions through c N ΔT , rather than the value of the tensions. This aspect is particularly useful in real case scenarios, as discussed [12], because large variations of cable tensions are not physically feasible.…”
Section: Constrained Optimization Problemmentioning
confidence: 99%
“…In the very last years, attention has been spent by a few researchers in the field of CDRs to apply the concepts of MPC ( [8], [9], [10], [11], [12]), also showing promising results. Different MPC architectures are proposed by these papers, with reference of fully constrained CDRs, and different approaches are proposed to deal with the nonlinear dynamic behavior of the system.…”
Section: Introductionmentioning
confidence: 99%